Ambulatory Catheter-based Interscalene Block for Proximal Humerus Fracture Rehabilitation: Safety, Efficacy and Lessons from a Pilot Study - Nah MFK; Seng ZQ; Tan YJB (Malaysian Orthopaedic Journal)
Introduction: Proximal humerus fractures (PHFs) are associated with morbidity/functional impairment. Rehabilitation adherence is crucial to regain independent function yet is often hindered by pain. This pilot study aims to analyse the safety and efficacy of ambulatory catheter-based interscalene blocks (CISBs) as analgesia in post-surgical PHF patients and summarise learning points to guide further implementation/study of ambulatory CISB. Materials and methods: This pilot study selected PHF patients who were >18yo, surgically treated and received ambulatory CISB (CISB ≥72 hours). Data was derived from clinical documentation (anaesthetist/surgeon/therapist reviews). Clinical outcomes (e.g. range of motion, Quick Disability of Arm/Shoulder/Hand (qDASH) scores), dynamic/resting pain scores and incidence of CISB-related complications were collected. Results: Twelve patients were selected with mean ambulatory CISB duration of 9.5 days. All patients improved clinically, with means improvements of +64.6° and +61.9° for passive flexion and abduction, and reduction of 29.8 in qDASH after 3 months. Two patients experienced neurological complications (phrenic nerve palsy; medial forearm numbness) while six patients experienced catheter-based complications (dislodgment, erythema). All complications were self-limiting, resolving with removal of catheter. Conclusion: Ambulatory CISB can minimise pain and facilitate rehabilitation for PHF patients. Learning points include (1) complications are predictable and incidence/physiological impact on patients can be minimised via appropriate patient selection, (2) standardised protocols (e.g. tunnelling of catheters) help maximise utility of ambulatory CISB while minimising complications, (3) regular monitoring/anticipation of complications facilitate early detection and prompt management. These learning points, combined with existing literature, can be adapted to future applications of ambulatory CISB to better study its safety and efficacy.